Entrepreneurship education: Orang Asli and learning experience - Zainal Adnan, Ahmad Amri; Mohd Rosdi, Siti Asma'; Samsudin, Norsamsinar (International Business Education Journal, 2020)
Understanding entrepreneurship concept is indispensable in formal education system to support entrepreneurship education especially in school and higher education institutions. However, the need to understand entrepreneurship concept is essential and important as every individual has the potential to be an entrepreneurs. This study aims to assess the understanding of entrepreneurship concept among Orang Asli after playing a game; and to remark the emotional connotation after playing the game. This paper employed qualitative method in the form of observation and interview with 20 Orang Asli Semai in Perak state. The findings indicated that most participants showed basic understanding of entrepreneurship and developed positive connotation while playing the game. The study drew attention to the importance of learning through playing in non-formal learning especially among the Orang Asli community.